Why do my patients still have early childhood caries? a critical appraisal - Luciana Butini OLIVEIRA; Flávio de Freitas MATTOS; Saul Martins PAIVA; Marcelo BÖNECKER (Brazilian Oral Research)
Abstract The prevalence of early childhood caries (ECC) tends to increase in the first 5 years of life as children grow, and those affected by ECC are likely to experience caries throughout their lives. ECC negatively impacts the oral health-related quality of life of both children and their families. Although controlling sugar intake and the use of fluoride are well-known methods for managing dental caries, preventive and therapeutic interventions alone have not been sufficient to prevent the development of new caries lesions. This review aims to explore why ECC continues to occur despite the oral health team having the necessary knowledge to prevent it. Based on current scientific evidence, this article highlights the need for the oral health team to consider additional factors, such as implementing oral health prevention programs in the first 450 days of life, enhancing caregivers’ oral health literacy, creating a supportive environment, and engaging in upstream actions (teledentistry, implementation science, health policies development etc.) to effectively manage and prevent dental caries. Otherwise we would be educating and treating children and sending them back to the conditions that made them sick. By addressing these factors, it might be possible to improve long-term oral health outcomes for children and reduce the burden of ECC on children and their families.